2018
DOI: 10.1007/s11356-018-2365-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of drilling waste from shale gas exploration in Central and Eastern Poland

Abstract: The purpose of this research was to determine and evaluate the chemical properties of drilling waste from five well sites in Central and Eastern Poland. It was found that spent drilling fluids can contain high values of nickel and mercury (270 and 8.77 mg kg respectively) and can exceed the maximum permissible limits recommended by the EC regulations for safety of soils (75 mg kg for nickel and 1.5 mg kg for mercury). The heavy metal concentrations in the studied drill cuttings did not exceed the maximum permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The drilling and completion of shale gas wells can generate large volumes of drilling wastes. , Drilling wastes consist of drill cuttings (shale rock pieces) usually enriched in trace metals/metalloids and/or NORMs as well as residual drilling muds which often contain elevated Ba (barite used as weighting agent) and various organic chemicals, such as base oil, polymers, and biocides. , The leaching of poorly managed drilling wastes by rainwater may release toxic elements into shallow groundwater through runoff (Figure ). Based on leaching experiments, several studies have evaluated the potential for the release of toxic trace elements and NORMs from exposing shale cuttings to surface conditions. ,,, These studies revealed that the oxidative dissolution of sulfide minerals and organic matter may be a significant source of dissolved trace metals/metalloids (e.g., As, Cd, Mo, Ni, and Zn) in leachates (Figure ).…”
Section: Potential Sources Of Inorganic Contaminants In Shallow Groun...mentioning
confidence: 99%
See 1 more Smart Citation
“…The drilling and completion of shale gas wells can generate large volumes of drilling wastes. , Drilling wastes consist of drill cuttings (shale rock pieces) usually enriched in trace metals/metalloids and/or NORMs as well as residual drilling muds which often contain elevated Ba (barite used as weighting agent) and various organic chemicals, such as base oil, polymers, and biocides. , The leaching of poorly managed drilling wastes by rainwater may release toxic elements into shallow groundwater through runoff (Figure ). Based on leaching experiments, several studies have evaluated the potential for the release of toxic trace elements and NORMs from exposing shale cuttings to surface conditions. ,,, These studies revealed that the oxidative dissolution of sulfide minerals and organic matter may be a significant source of dissolved trace metals/metalloids (e.g., As, Cd, Mo, Ni, and Zn) in leachates (Figure ).…”
Section: Potential Sources Of Inorganic Contaminants In Shallow Groun...mentioning
confidence: 99%
“…42,77 Drilling wastes consist of drill cuttings (shale rock pieces) usually enriched in trace metals/metalloids and/or NORMs as well as residual drilling muds which often contain elevated Ba (barite used as weighting agent) and various organic chemicals, such as base oil, polymers, and biocides. 42,91 The leaching of poorly managed drilling wastes by rainwater may release toxic elements into shallow groundwater through runoff (Figure 1). evaluated the potential for the release of toxic trace elements and NORMs from exposing shale cuttings to surface conditions.…”
Section: Geological and Geochemical Characteristics Of Shale Reservoirsmentioning
confidence: 99%
“…The legal regulations in the European Union do not allow the application of drilling wastes onto the land surface, in contrast to the law in Canada or the United States. Thus, in Poland, these methods are not employed [ 13 ], although adding drilling wastes to soils seems to be a convenient method of their management.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the West Texas area, the Ni contents in flowback water, disposal wells and waste pit samples range from 3.06 to 4.78 mg L −1 (Thacker et al., 2015). High levels of Ni were also detected in drilling cuttings and its runoff liquid (Mikos‐Szymanska et al., 2018; Wang et al, 2017). The Ni contents in drilling cuttings and drilling fluid samples in central and eastern Poland range from 24 to 71 mg kg −1 and 16 to 270 mg kg −1 , respectively (Mikos‐Szymanska et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…High levels of Ni were also detected in drilling cuttings and its runoff liquid (Mikos‐Szymanska et al., 2018; Wang et al, 2017). The Ni contents in drilling cuttings and drilling fluid samples in central and eastern Poland range from 24 to 71 mg kg −1 and 16 to 270 mg kg −1 , respectively (Mikos‐Szymanska et al., 2018). The Lower Cambrian Niutitang Formation shale, a promising shale gas target zone in southwest China, could possibly have Ni enrichment (Neelameggham et al, 2014; Wang & Zhang, 2016).…”
Section: Introductionmentioning
confidence: 99%